Пространство и время в повести Александра Солженицына Адлиг Швенкиттен - Павеелева, Елена (Acta Polono-Ruthenica, 2021)
Many literary works of Alexandr Solzhenitsyn have an autobiographical basis. Allenstein (present-day Olsztyn) is one of the important points in Solzhenitsyn’s personal life which led to the Nobel Prize and worldwide fame for the writer. Allenstein becomes one of crucial spatial points that organize the plot of Solzhenitsyn’s military story Adlig Schwenkitten. This work has a very characteristic subtitle, “A Tale of 24 Hours”. The subtitle indicates the time of the story. The header contains information about spatial (geographic) coordinates. This is a narrow local area in East Prussia. The forward units of heavy artillery troops move here, while the infantry and rear services remain far behind. The chronotope of the story is set in an extremely specific way already in the title itself: the title defines the spatial coordinates, and the subtitle defines the temporal coordinates. In artistic terms, these are the moments that characterize the plot specificity of the story. The writer transforms the events of his life with the help of artistic means. This transformation becomes a landmark phenomenon in literature. Behind the usual details, you can see the whole artistic universe, which, as the writer said, is connected “with the fundamental principles of human existence”.